Eu-Doped Gd2MoB2O9 Phosphors for Latent Fingerprints Detection. Issue 1 (4th May 2022) - Chamchoi, N.; Sangwaranatee, N.; Rajaramakrishna, R.; Kim, H. J.; Chaemlek, O.; Limsuwan, P.; Kaewkhao, J.
Abstract: The luminescent powders from rare-earth ions doped oxides have been successfully used for latent fingerprint detection due to high efficiency, high contrast and low background interface. The Gd2 MoB2 O9 :Eu 3+ phosphors with varying compositions of Eu 3+ ions were synthesized by solid state reaction method. These phosphors were investigated by X-ray diffraction (XRD), diffuse reflectance spectroscopy, photoluminescence (PL), and decay curves studies. Multiphoton relaxation decay rate and coupling strength was evaluated using phonon side band spectrum showing 0.4 mol% doped samples show less non radiative decay rate. The 0.40 mol% of Eu 3+ ion concentration doped in the Gd2 MoB2 O9 host lattice show highest photoluminescence emission intensity at 613 nm, in orange red region, monitored at 394 nm excitation. The Gd2 MoB2 O9 :Eu 3+ phosphors samples were optimized to 900 °C sintering temperature and optimum milling time at 3 min in the present work. The latent fingerprints detection that developed from Gd2 MoB2 O9 :Eu 3+ phosphors in this work exhibited clearly ridge characteristics under UV illumination. The results revealed thatGd2 MoB2 O9 :Eu 3+ phosphors are potential practical forensic science applications.